IDENTIFIKASI DAN UJI AKTIVITAS DAYA HAMBAT EKSTRAK ETANOL BIJI PINANG (Areca catechu L.) TERHADAP ISOLAT BAKTERI GUSI: IDENTIFIKASI DAN UJI AKTIVITAS DAYA HAMBAT EKSTRAK ETANOL BIJI PINANG (Areca catechu L.) TERHADAP ISOLAT BAKTERI GUSI - rina Lestari; meiriza djohari; Syilfia Hasti (Jurnal Penelitian Farmasi Indonesia)
Periodontal prevalence in all age groups in Indonesia is 96.58%. The main cause ofperiodontal is microorganisms in dental plaque. Control of plaque reduction can be done using natural ingredients which contain antibacterial, one of which is areca nut seed (Areca catechu L.). This research aims to determine the type of bacteria on the gums, and to determine the antibacterial activity of ethanol extract of areca nut (Areca catechu L.) on gums' bacteria isolate. Antibacterial activity test used Agar diffusion method with concentration series 10%, 20%, 30%. The results of phytochemical screening of areca nut seed ethanol extract showed the presence of alkaloids, terpenoids and flavonoids. The results from the identification test based on macroscopic, microscopic, and biochemical observations obtained two Gram-positive bacteria (Staphylococcus epidermidis and Streptococcus sp) and one Gram-negative bacteria (Enterobacter aerogenes). Antibacterial activity test of ethanol extract of areca nut seed (Areca catechu L.) on gums' bacterial isolates was analyzed statistically with One Way Anovaand alternative test withKruskal-Wallis . Antibacterial activity of ethanol extract of areca nut seed (Areca catechu L.) on Staphylococcus epidermidis and Streptococcus spbacteria at concentrations of 10%, 20%, and 30% showed significant difference diameter of inhibitory power compared to positive and negative controls on Enterobacter aerogenes bacteria at concentration of 10 %, 20%, and 30% showed that the diameter of inhibitory power was significantly different compared to positive controls and not significantly different compared to negative controls.